Unlocking the ecotourism environment: exploring music as a tool for cultural preservation and sustainable tourism development - Agus Cahyono; Fajry Sub'haan Syah Sinaga; Sunarto Sunarto; Udi Utomo; Syahrul Syah Sinaga (Institut Seni Indonesia Surakarta, 2023)
This qualitative research study investigates the role of music as a catalyst for fostering sustainable tourism practices and contributing to the long-term social, economic, and environmental well-being of ecotourism destinations. The focus is on Truthung's musical performances in Magelang, which serve as reflections of local tourism potential and the surrounding natural environment, including the Borobudur Temple and the Merapi, Merbabu, Andong, Sumbing, and Menoreh Mountains. Drawing upon the interdisciplinary concept of ecomusicology, this study employs various data collection methods, including observations, interviews, and documentation. By examining the growth and development of Truthung Music performances, with a particular emphasis on key figures such as Sutanto Mendut and farming artists from Merbabu, this research sheds light on the transformative power of music within the local community. The findings reveal that Truthung Music not only represents the rich local environment and culture within tour packages in Magelang Regency but also emphasizes the broader interplay between nature and culture.